The Feminisation of Indonesia’s Political Parties: Toward Feminised Parties? - Esty Ekawati; Sri Budi Eko Wardani; Lili Romli; Nur Iman Subono (JSP: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The political representation of women in the Indonesian parliament has increased since the implementation of the affirmation policy through quotas, although the number has not yet reached 30%. In addition, the percentage of women placed in the management structure of political parties has also increased. In addition, the percentage of women's candidacy in each election period also showed an increasing trend. This article aims to analyse the feminisation process that occurred in ten political parties in the Indonesian reform era using the model of party responsiveness introduced by Lisa Young. By using a qualitative approach, in which data were obtained from interviews, party statutes (AD/ART), and documents of the Special Committee for the 2017 Election Bill, it was found that the feminisation of political parties in Indonesia is divided into two categories, namely responsive and co-optive. The difference in the level of feminisation is due to differences in party responses to three things namely, the number of women in the party’s structure, quota rules, and party responses to pro-women policies. Based on the mapping of political parties in Indonesia using a model of party responsiveness, it can be said that political parties experience limited feminisation where only the representational dimension shows a high tendency. However, in the policy dimension, most parties have a negative response. Therefore, the feminisation that occurs is half-hearted.